Preparation of Gd Complex-Immobilized Silica Particles and Their Application to MRI. (10th April 2013) - Kobayashi, Yoshio; Morimoto, Hikaru; Nakagawa, Tomohiko; Kubota, Yohsuke; Gonda, Kohsuke; Ohuchi, Noriaki
Abstract : A preparation method for Gd-ethylenediaminetetraacetic acid disodium salt dihydrate (ETDA) complex-immobilized silica particles (Gd-EDTA/SiO2 ) is proposed. Preparation of spherical silica particles was performed by a sol-gel method at 35°C using 0.2 M tetraethylorthosilicate, 25 M H2 O, and 0.01 M NaOH in ethanol, which produced silica particles with an average size of 80 . 4 ± 14 . 9  nm. Immobilization of Gd-EDTA on the silica particles was conducted at 35°C by introducing amino groups on the silica particles with (3-aminopropyl)trimethoxysilane at pH 3 (NH2 /SiO2 ) and then making Gd-EDTA act on the NH2 /SiO2 particles at pH 5. The as-prepared Gd-EDTA/SiO2 particle colloid solution was concentrated up to a Gd concentration of 0.347 mM by centrifugation. The sphere structure of Gd-EDTA/SiO2 particles was undamaged, and the colloid solution was still colloidally stable, even after the concentrating process. The concentrated Gd-EDTA/SiO2 colloid solution revealed good MRI properties. A relaxivity value for T1 -weighted imaging was as high as 5.15 mM −1  s −1, that was comparable to that for a commercial Gd complex contrast agent.